Epidemiological aspects of human rotavirus infection in children hospitalized with acute gastroenteritis in an area of northern Italy - Medici, M.C.; Martinelli, M.; Arcangeletti, et al., M.C. (Acta Biomedica Atenei Parmensis, 2004)
Human rotavirus (HRV) is recognized as the most common cause of severe gastroenteritis in children under 5 years of age. Due to the lack of recent reports about the surveillance of HRV infection in Italy, in this study we assessed the prevalence rate of HRV infection on 1,340 stool samples belonging to 1,264 pediatric patients hospitalized with acute gastroenteritis in the period January 2000-December 2002. The stool samples were submitted to virological investigations by electron microscopy (EM) and conventional cell culture, as well as from January 2002 by RT-PCR for norovirus detection. Reovirus-like particles observed by EM were identified by electropherotyping. Single HRV infections were detected in 302 cases (23.9%, ranging from 19.1% in 2000 to 30.2% in 2001). Mixed infections were observed in 28 cases in which HRV was found to be associated with adenovirus in 16 cases (1.3%), with picornavirus in 4 (0.3%), and with norovirus in 8 (2.1% of the 388 cases examined in 2002). The 3 major epidemic periods of HRV infections were March-May 2000 (66 cases), December 2000-May 2001 (128 cases) and September 2001-April 2002 (105 cases) with peaks in March, January and March, and January, respectively. In the periods of major incidence, single HRV infection accounted even for 52.5% of the gastroenteritis cases monthly examined. According to age distribution, 68.9% (208 cases) of HRV infected children was under 4 years (69.6%: 230/330 cases, including mixed infections) and 16.9% (51 cases) was in the 5-12-year age group. The epidemiological aspects of HRV infection, also compared to other enteric virus infections, will contribute to assess the magnitude of the problem of HRV in different settings and to devise strategies for intervention.